Cryptology and network security : 15th International Conference, CANS 2016, Milan, Italy, November 14-16, 2016, proceedings /: 15th International Conference, CANS 2016, Milan, Italy, November 14-16, 2016, proceedings. (2016) - Unknown
No abstract available